Preparation of Microporous PVDF Hollow Fiber Membrane Contactors for CO2 Stripping from Diethanolamine Solution - Rosmawati, Naim; Ahmad Fauzi, Ismail; Mansourizadeh, A. (Elsevier Ltd., 2012)
Microporous polyvinylidene fluoride (PVDF) hollow fiber membranes were fabricated via a wet-spinning process. The prepared fibers were characterized in terms of contact angle, gas permeability, wetting pressure and morphology. CO2 stripping from preloaded aqueous diethanolamine solution was conducted through the gas–liquid membrane contactors. The effects of lithium chloride (LiCl) concentration on the membrane properties and CO2 stripping performance were investigated. The addition of different LiCl concentration resulted in a less finger-like structure, with highly effective surface porosity and high wetting pressure. Conversely, N2 permeability, contact angle value and membrane pore size were reduced as the concentration of the additives were increased. For stripping flux performance, membrane with 5 wt% LiCl demonstrated the highest flux of 1.61 × 10−2 mol/m2 s at 110 ml/min of the liquid flow rate. It was found that the membrane with less finger-like structure and higher effective surface porosity exhibited higher stripping efficiency. These results suggest that developed membrane structure can be an alternative for the CO2 stripping through gas–liquid membrane contactors.